Early sport specialization trends and injuries in former high school athletes specialized in sports - Nagano, Y.; Oyama, T. (Open Access Journal of Sports Medicine, 2023)
Purpose: Determining the effects of early specialization in a specific sport is difficult. Therefore, it is necessary to investigate its effects based on the type of sports. The purpose of this study was to investigate the proportion of participants who had been participating in a single sport, in individual or team sports from an early age and to compared the prevalence of acute and overuse injuries among these participants.